2022
DOI: 10.1016/j.pcad.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Shelter from the cytokine storm: Healthy living is a vital preventative strategy in the COVID-19 era

Abstract: Coronavirus disease 2019 (COVID-19) continues to have a devastating effect on a global scale. COVID-19 variants continue to arise and counteract vaccination efficacy. As such, preventative health measures, such as social distancing and stay at home mandates, will continue for the foreseeable future. Evidence on those at greatest risk for poor outcomes if infected with COVID-19 has rapidly come to light. It has become clear that those with unhealthy lifestyle characteristics, chronic disease risk factors and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“… 1 , 4 , 5 In this context, decades of unhealthy lifestyle behaviors, both independently and through the association with chronic disease risk factors, primed the pump for poor COVID-19 outcomes. 1 , 6. , 7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 4 , 5 In this context, decades of unhealthy lifestyle behaviors, both independently and through the association with chronic disease risk factors, primed the pump for poor COVID-19 outcomes. 1 , 6. , 7.…”
mentioning
confidence: 99%
“… 33 Numerous health benefits directly relevant to infectious diseases are associated with being physically active, one of which is lower levels of systemic inflammation. 34 , 35 Poor outcomes with SARS-CoV-2 have been associated with a cytokine storm, 6 and elevated systemic inflammation prior to infection may foretell an increased risk for this storm and an untoward clinical course. 36 There is some evidence to indicate systemic inflammation levels are lower in the sub-Saharan African population.…”
mentioning
confidence: 99%
“…Rationale: COVID-19 has a direct impact upon the cardio-respiratory systems and its sequelae have broad implications for exercise intolerance and healthy lifestyle behaviours. 5 , 41 The incidence of PH may increase post-pandemic. 42 Therefore, it is important to understand the factors that contribute to chronic exercise intolerance among those infected by the virus.…”
Section: Previously Established Research Prioritiesmentioning
confidence: 99%
“…, 4. , 5. related chronic diseases and co-morbidities, which can increase disease severity if infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus responsible for COVID-19.…”
mentioning
confidence: 99%
“… 12 , 15 Findings from a recently published comparative risk assessment study found that nearly 64% of the >900,000 COVID-19 hospitalizations occurring in the US through November 2020 were attributable primarily to obesity (30.2%), hypertension (26.2%), and T2D(20.5%), suggesting that the majority of hospitalizations could have been prevented if these conditions were not present. 8 Individuals with obesity were found to have increased risk of COVID-19 hospitalization and severe illness similarly across the lifespan in adults 2 , 8 as well as in children and adolescents 16 — an observation that is not surprising given the role of obesity in inciting inflammation, 17 and impairing the immune response as evidenced in prior disease-related pandemics (e.g., 2009 H1N1 Influenza A Virus). 18 Of grave concern were the well documented higher cases of COVID-19 19 among racially and ethnically minorized communities with whom already had unequal burden due to the higher prevalence of cardiometabolic comorbidities 20 and are more likely to suffer worse outcomes, 21.…”
mentioning
confidence: 99%